Bone Tendon Interface: A New Perspective on Rotator Cuff Healing. Issue 11 (27th November 2019) - Sun, Yucheng; Kholinne, Erica; Jeon, In-Ho
During rotator cuff repair surgery, fixation and incorporation of ruptured rotator cuff tendon into the bone is a major concern. Many studies have report the limitations in the healing potential of the bone-tendon interface. The structure and composition of the native direct bone-tendon interface cannot be restored after primary repair, resulting in a poor mechanical and structural interface and leading to a high rate of re-tear (95%) especially after in larger or massive tear (Figure 1). If the native bone-tendon junction cannot be regenerated after primary repair, a bone-tendon composite graft, which preserves the native bone-tendon junction, can be a valuable option. Thus, we have adopted the concept of bone to bone and tendon to tendon healing by using autogenous bone-tendon composite graft. The Achilles-calcaneus composite autograft group showed significantly better biomechanical characteristics at 3 and 6 weeks in terms of maximum load, maximum stress, stiffness, and Young's modulus. Tissue histology demonstrated an organized extracellular matrix, a clear tide mark, and distinct fibrocartilage layers in the composite graft group, similar to those of the native bone-tendon interface (Figure 2). Additionally, clear bone to bone healing and tendon to tendon healing were observed. By contrast, the conventional primary repair could not regenerate the structure of the native bone-tendon interface, although bone-tendon interface healing progressed. Bone-tendon autograft for chronic rotator cuff reconstruction is superior to the primary repair regarding biomechanical property and histological structure. : Figure 1. Rat model showing (Left) Native bone tendon interface showing distinct layer of tendon – unmineralized fibrocartilage – mineralized fibrocartilage – lamellar bone. (Right) Bone tendon interface following primary repair for chronic rotator cuff tear. Figure 2. Rat model of primary repair and composite graft rotator cuff repair.